Comparison of the LMA-ProSeal and LMA-Classic in Children (Delta Medical College Journal, 2018)
Background: The LMA-ProSeal is a new laryngeal mask airway with a rear cuff and drainage tube that allows a higher seal pressure than the LMA-Classic for the same intra-cuff pressure and it permits drainage of gastric secretions and access to the alimentary tract.Objective: This study compared the LMA-ProSeal and LMA-Classic in children for ease of insertion, airway sealing pressure and maintenance of airway.Materials and method: This comparative study was done during the period of January 2015 to December 2015 in BIRDEM Hospital, Dhaka, Bangladesh. Forty ASA 1-2 children undergoing circumcision, herniotomy and orchiopexy were included. The patients were randomly assigned to size 2.5 LMA-ProSeal or 2.5 LMA-Classic groups for airway management. We assessed success rates at first attempt of insertion, airway sealing pressure, maintenance of airway and postoperative complications.Results: There was no statistical difference between two groups for the success rates at first attempt of insertion and maintenance of airway but sealing pressure was significantly high in the LMA-ProSeal group. Regarding postoperative complication like injury to lip-teeth-tongue, blood staining and cough or laryngospasm were also not significant.Conclusion: We concluded that ease of insertion, maintenance of airway and risk of injury are similar between the LMA-ProSeal and the LMA-Classic in children.Delta Med Col J. Jan 2018 6(1): 18-21